Morpho-physiological Responses of Chilli (Capsicum annuum L.) to Foliar Application of Micronutrients and Growth Regulators - Ghosh, Arindam; Mondal, Sananda; Panda, Debasish (International Journal of Bio-resource and Stress Management, 2020)
A field experiment was conducted at Agriculture Farm of Institute of Agriculture, Visva-Bharati, Sriniketan to study the effect of micronutrients and growth regulators on chilli during rabi 2015-16 and 2016-17. Five levels each of different micronutrients (Control, 0.1% ZnSO4, 0.2% ZnSO4, 0.1% H3BO4 and 0.2% H3BO4) and growth regulators (Control, 0.5 ppm 28-Homobrassinolide, 1 ppm 28-Homobrasinolide, 10 ppm Putrescine, 20 ppm Putrescine) were used for foliar application to chilli plants. Growth parameters such as plant height, dry matter accumulation and number of branchesplant-1 as well as physiological parameters such as leaf area index and crop growth rate were recorded during both the years. The experimental finding revealed that application of micronutrients such as Zinc (ZnSO4) and Boron (H3BO4) as well as growth regulators (28-Homobrassinolide and Putrescine) improved both growth and physiological parameters of chilli. Among the micronutrients, the highest value of the growth parameters such as plant height, dry matter accumulation, number of branches plant-1 and physiological parameters such as LAI and CGR were recorded from the application of 0.2% ZnSO4 followed by 0.1% ZnSO4 and 0.2% H3BO4; whereas, among the growth regulators highest value of these parameters were recorded from the application of 0.5ppm of 28-Homobrassinolide followed by 1 ppm of 28-Homobrassinolide. Application of 0.2% ZnSO4 also recorded highest number of fruits plant-1 and fruit yield plant-1. Highest values of these yield attributes were also recorded from the application of the growth regulator 28-Homobrassinolide (0.5 ppm).